Rapid construction and advanced technology for a Covid-19 field hospital in Wuhan, China. Issue 1 (10th September 2020) - Zhou, Man; Chen, Yaying; Su, Xiaolong; An, Ling
Abstract : A specialised emergency field hospital was constructed in record time in Wuhan, China shortly after the initial outbreak of the Covid-19 pandemic. Covering an area of 34 000 m 2 and providing 1000 beds, Huoshenshan Hospital was more advanced and had more rigorous isolation systems than most current infectious-disease hospitals, but it was delivered in just 10 days. The rapid construction benefited from a unique modular design, over 4000 people who worked around the clock and a series of advanced technologies such as building information modelling, modular construction and 5G communications. The hospital played a crucial role in controlling the pandemic in China.